Reclaiming the Rights of the Hobbesian Subject - Curran, Eleanor. author. aut Link
XIII, 205 p.
Keywords: 'There are no substantive rights for subjects in Hobbes's political theory, only bare freedoms without correlated duties to protect them'. Curran challenges this orthodoxy of Hobbes scholarship, and argues that Hobbes's theory is not a theory of natural rights but rather, a modern, secular theory of rights, with relevance to modern rights theory.